Internationalisation, professional practice and student campus life : a comparative study of two academic departments in a South African university. - Tang, Qishan (My University, 2014)
This is a comparative study on postgraduate students‘ social experiences in two academic departments: the Faculty of Health Sciences and the Wits School of Business, at the University of the Witwatersrand (Wits), South Africa. This study‘s central questions are: how do postgraduate students from two departments perceive their social experiences? What shaped their perceptions? And how do they compare? This study shows a difference in students‘ perceptions and understandings of the social space in those departments. That is, social interactions at the business school (Wits School of Business) are closely linked to the academic space with the patterns linked to having friends from the same classes and study groups with very high expectations of social life on campus; while in the Faculty of Health Sciences, social interactions are limited and socially orientated with the patterns of having friends from the same department and same region with low expectations on their social life. This difference is explained by means of two main factors, the nature of the academic discipline and the students‘ individual identities that they bring to campus.
Keywords: Internationalisation; Higher education; Students' social experience; Social identity; Social identity theory